Determination of energy level alignment at metal/molecule interfaces by in-device electrical spectroscopy - Gobbi, M. (2014)
The energetics of metal/molecular semiconductor interfaces plays a fundamental role in organic electronics, determining the performance of very diverse devices. So far, information about the energy level alignment has been most commonly gained by spectroscopy techniques that typically require experimental conditions far from the real device operation. Here we demonstrate that a simple three-terminal device allows the acquisition of spectroscopic information about the metal/molecule energy alignment in real operative condition. As a proof of principle, we employ the proposed device to measure the energy barrier height between different clean metals and C60 molecules and we recover typical results from photoemission spectroscopy. The device is designed to inject a hot electron current directly into the molecular level devoted to charge transport, disentangling the contributions of both the interface and the bulk to the device total resistance, with important implications for spintronics and low-temperature physics.